Evaluation of CD10 expression as a diagnostic marker for colorectal cancer - Żurawski, Jakub; Talarska, Patrycja; de Mezer, Mateusz; Kaszkowiak, Krzysztof; Chalcarz, Michał; Iwanik, Katarzyna; Karoń, Jacek; Krokowicz, Piotr (Gastroenterology and hepatology from bed to bench, 2022)
We aimed to determine the potential of CD10 as a marker for the early diagnosis of adenocarcinoma of the colon. Adenocarcinoma is diagnosed in one out of 20 individuals in the USA and western European countries. Its prognosis and treatment depend largely on the severity of the disease at the time of diagnosis. Additional new biological markers are being sought that can help diagnose colon cancer at an early stage. One such marker present in both serum and tumor tissue is CD10. CD10 concentrations were tested by ELISA and immunohistochemistry in serum and tissue samples, respectively, from 113 patients diagnosed histopathologically and treated for adenocarcinoma of the colon. Additionally, the ROC curve with optimal cut-off point based on Youden's criterion was calculated for CD10. Serum concentrations of CD10 and its tissue expression in patients diagnosed with adenocarcinoma of the colon correlate with cancer staging based on the Astler-Coller-Dukes classification. To ascertain the optimal cut-off point for CD10 as a predictor of belonging to the study group, ROC curve was prepared for CD10. Optimal cut-off point for CD10 was 0.57, with prediction of belonging to the study group for CD10 ≥ 0.57. CD10 can be a useful marker in the early diagnosis of adenocarcinoma of the colon.